Establishing a controlled hookworm human infection (CHHI) model for Africa: A report from the stakeholders meeting held in Lambaréné, Gabon, November 10-11, 2019 - Ayodele Alabi; Mosarrof Hussain; Marie-Astrid Hoogerwerf; Christine Ndong Mengome; Moses Egesa; Emmanuella Driciru; Linda J. Wammes; Yvonne C. M. Kruize; Erliyani Sartono; Ayola Akim Adegnika; Peter G. Kremsner; Maria Yazdanbakhsh; et al. (BMC, 2021)
Abstract Background Hookworm is a major contributor to worldwide disease burden with over 230 million people infected. It has been identified as one of the Neglected Tropical Diseases that can be controlled and even eliminated through mass drug administration and other effective interventions. Mathematical models have shown that hookworm can only be eliminated via a vaccine. Controlled Hookworm Human Infection (CHHI) models can facilitate rapid development of vaccines and drugs. Methods As a first step towards the establishment of CHHI in Africa, we held a stakeholders meeting in Lamberene, Gabon from 10 to 11 November 2019. Results Discussions revolved around the roles of the different regulatory institutions concerned; the need to strengthen existing regulatory capacity and the role of legislation; creating Gabon-specific ethical guidelines to govern Controlled Human Infection (CHI) studies; development of a study protocol; consideration of cultural and social peculiarities; the need for regular joint review meetings between interested parties throughout the process of protocol implementation; and participant compensation. Moreover, operational considerations concerning the introduction of CHHI in Gabon include the use of the local strain of hookworm for the challenge infections, capacity building for the local production of challenge material, and the establishment of adequate quality assurance procedures. Conclusion The workshop addressed several of the anticipated hurdles to the successful implementation of CHHI in Gabon. It is our aim that this report will stimulate interest in the implementation of this model in the sub-Saharan African setting.